2017
DOI: 10.1016/j.jfoodeng.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

How does particle size influence caking in lactose powder?

Abstract: Particle size distribution (PSD) is known to influence product properties such as flowability and compressibility. When producing crystalline lactose, different steps can affect the PSD of the final powder. The aim of this study was to investigate the influence of PSD on caking and the mechanisms involved. Smaller particles showed higher moisture sorption and a greater caking tendency, measured by dynamic vapor sorption and ring shear testing, respectively. Therefore, moisture sorption isotherms appeared as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 25 publications
2
22
0
2
Order By: Relevance
“…Mineral content of DWP and WPP was also significantly higher (P ≤ 0.05) in smaller size fractions. In a similar study by Carpin et al (2017), the authors also observed higher protein and mineral contents for smaller particles of crystalline lactose powder. As expected, DWP and WPP contained a higher amount of lactose (80.2 ± 1.27 and 87.3 ± 0.83%, respectively) compared with SMP (48.5 ± 6.11%).…”
Section: Particle Size Fractions and Bulk Composition Of Powdersmentioning
confidence: 60%
See 2 more Smart Citations
“…Mineral content of DWP and WPP was also significantly higher (P ≤ 0.05) in smaller size fractions. In a similar study by Carpin et al (2017), the authors also observed higher protein and mineral contents for smaller particles of crystalline lactose powder. As expected, DWP and WPP contained a higher amount of lactose (80.2 ± 1.27 and 87.3 ± 0.83%, respectively) compared with SMP (48.5 ± 6.11%).…”
Section: Particle Size Fractions and Bulk Composition Of Powdersmentioning
confidence: 60%
“…Haque and Roos (2004b) examined the differences in water uptake of coarse and fine amorphous lactose/protein powders and found that the fine particles absorbed slightly more water than the coarse powder particles at relative vapour pressures (RVP) ≤ 33.2%. Similarly, Carpin et al (2017) found that for crystalline lactose powders, smaller particles showed an increase in water absorption compared with larger particles at RHs > 50%. Rogé and Mathlouthi (2000) also showed the same effect of particle size on water uptake for crystalline sucrose.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The filled pans were subjected to water adsorption cycle using surface measurement DVS advantage (Surface Measurement Systems Ltd., London, UK) equipped with a Cahn microbalance. The DVS program was setup as described by Carpin et al (2017). The lactose crystallization characteristics [water activity and necessary water for lactose crystallization (X c )] were identified.…”
Section: Dynamic Vapor Sorptionmentioning
confidence: 99%
“…Besarnya jumlah partikel yang pada ukuran 125 µm dapat juga dikarenakan partikel tersebut saling menempel dan tidak dapat lepas dari saringan, Distribusi ukuran partikel diukur untuk memastikan kualitas konstan tepung, flowability, kepadatan, kompresibilitas yang artinya bahwa semakin tinggi partikel halus (yang <250 µm) maka semakin banyak yang dapat terabsorpsi. Berdasarkan penelitian ini didapatkan data bahwa ukuran partikel yang lebih kecil <250 µm adalah berkisar 7)% sehingga dapat diasumsikan bahwa tepung Okra dapat terabsorbsi dengan baik (Carpin et al, 2017). Kadar air buah Okra yaitu 89,7%, sedangkan tepung Okra memiliki kadar air 8,37% (Tabel 2).…”
Section: Analisis Particle Size Distributionunclassified